PENGARUH ETOS KERJA, DISIPLIN DAN PENGEMBANGAN KARIR TERHADAP KINERJA KARYAWAN CU TALENTA PEMATANG RAYA - Purba, Bella; Tinambunan, Anitha Paulina (LPPM Universitas Katolik Santo Thomas Medan, 2023)
This study aims to determine and explain the influence of work ethic, discipline and career development on the performance of CU employees Raya Talent. Data collection was carried out through questionnaires and documentation techniques. The research method used is quantitative, with 32 respondents taken using saturated or census sampling. Data analysis in this study used SPSS version 23. From the partial test results the t test shows tcount 2.716 > ttable 1.701 and the significance level is 0.011 < 0.50 proving that work ethic has a positive and significant effect on employee performance. tcount 4.213 > ttable 1.701 and a significance level is 0.000 < 0.50 proving that discipline has a positive and significant effect on employee performance. tcount 2.717 > ttable 1.701 and a significance level is 0.11 < 0.50 proving that career development has a positive and significant effect on employee performance. The F test shows Fcount 46.232 > Ftable 2.67 with a significance level of 0.000 < 0.05 proving that work ethic , discipline and career development have a positive and significance effect on employee performance. The coefficient of determination (R Square) of 0.826 means that employee performance can be explained by work ethic , discipline and career development by 82.9% while another 17.1% can be explained by other variables that are not included in this study such as training and selection.